Extent of CSR Adoption among Indian Small and Medium Enterprises - Bynipudi, Michael Harshavardhan (International Journal of Psychosocial Rehabilitation, 2020)
The impact and role of Micro, Small and Medium Enterprises (MSMEs) in the development of economy means that, it becomes difficult to dismiss the importance of the latter in such important socially relevant issues as employment, innovation and living standards. This research mainly focuses on examining the extent of CSR Adoption among Indian Small and Medium Enterprises. The current CSR literature on MSMEs shows that a greater understanding of MSMEs' adoption is required. MSMEs have a major role to play in the economic growth and future development of developing countries like India. Considering India's geographical diversity and strong reliance on agriculture, MSMEs are the lifeline of potential economic growth and production. The current state of knowledge and practice in MSMEs in the Indian context in the area of CSR is however limited. The following study analyses quantitative data (300) information collected from the owners and managers of SMEs in the Tourism Sector from Hyderabad city using questionnaire forms. The results of the empirical study show that although the vast majority of SMEs is not familiar with the term CSR, most of them show practicing some of its activities. The results also revealed that only the size and age of SMEs influenced their CSR implementation.